2018
DOI: 10.1007/s00464-018-6077-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of premedication on lesion detection rate and visualization of the mucosa during upper gastrointestinal endoscopy: a multicenter large sample randomized controlled double-blind study

Abstract: BackgroundPremedication in upper gastrointestinal endoscopy for higher lesions detection rate has not been well studied so far. This study aimed to confirm whether premedication could improve the detection rate of early cancer or precancerous lesions and mucosal visibility.MethodFrom July 2015 to December 2015, 7200 participants from 6 centers were screened by endoscopy with one of the 4 following premedications randomly: (1) water (group D); (2) pronase (group A); (3) simethicone (group B); (4) pronase and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 18 publications
(21 reference statements)
2
38
1
Order By: Relevance
“…We agree with their concerns based on reports of crystallization in the endoscope channels when simethicone is used in the water pump. 3 The concentration of simethicone used varies and is not standardized, but frequently 10 to 20 mL (1-2 g) are poured into 1 liter of water. Then the water is flushed; applied on the mucosa covered with bubbles, mucus, or both; and directly suctioned.…”
Section: Responsementioning
confidence: 99%
“…We agree with their concerns based on reports of crystallization in the endoscope channels when simethicone is used in the water pump. 3 The concentration of simethicone used varies and is not standardized, but frequently 10 to 20 mL (1-2 g) are poured into 1 liter of water. Then the water is flushed; applied on the mucosa covered with bubbles, mucus, or both; and directly suctioned.…”
Section: Responsementioning
confidence: 99%
“…Published data from institutions in the United Kingdom have shown that 10-14% of gastric cancer patients had undergone EGD in the preceding 3 years [2,3]. Impaired visibility may be a paramount factor for missing diagnosis of EGD [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that premedication with antifoam/mucus agent before EGD can improve operation visibility [5][6][7]. Premedication with pronase [7][8], N-acetylcysteine [9] or simethicone [4] before EGD improves procedural visibility. In addition, combining different antifoam/mucus agents might be more effective [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations